다중 신호원에 대한 닫힌 형태 기반 3차원 위치 추정 - 고요한; Yo-han Ko; 부성춘; Sung-chun Bu; 이철수; Chul-soo Lee; 임재욱; Jae-wook Lim; 채주희; Ju-hui Chae (한국항행학회논문지, 2022)
본 논문에서는 다중 신호원이 존재하는 경우에 닫힌 형태 기반의 3차원 위치 추정 기법을 제안한다. TDOA나 AOA, FDOA와 같은 일반적인 위치 추정 기술은 단일 신호원이 존재하는 경우에 위치를 추정할 수 있으며, 미상의 다중 신호원이 존재하는 경우에 이를 구분하여 위치를 추정하는데 한계가 있다. 제안된 기법은 배열 안테나를 갖는 센서에 수신된 신호의 상호상관 벡터를 계산하고, 상호 상관 값으로부터 TDOA값과 AOA값을 추정한다. 그리고 기준 센서의 위치를 이용하여 좌표 변환을 수행하고, 변환된 좌표에 대해 추정된 AOA값을 이용하여 좌표 회전을 수행한 후 각 신호원에 대한 3차원 위치를 추정한다. 제안된 기법은 컴퓨터 모의실험을 통해 그 성능을 검증한다. In this paper, we propose a closed-form based 3D localization method in the presence of multiple signal sources. General localization methods such as TDOA, AOA, and FDOA can estimate a location when a single signal source exists. When there are multiple unknown signal sources, there is a limit in estimating the location. The proposed method calculates a cross-correlation vector of signals received by sensors having an array antenna, and estimates TDOA and AOA values from the cross-correlation values. Then, the coordinate transformation is performed using the position of the reference sensor. Then, the coordinate rotation is performed using the estimated AOA value for the transformed coordinates, and then the three-dimensional position of each emitter is estimated. The proposed method verifies its performance through computer simulation.